Pengaruh Kompetensi Objektivitas dan Tekanan Anggaran Waktu Terhadap Kualitas Hasil Audit Pada Perwakilan BPKP Provinsi Kepri - Nitha, Puspa; Wage, M. Sunarto (SCIENTIA JOURNAL, 2022)
The purpose of this study was to determine the effect of competence, objectivity and time budget pressure on the quality of audit results and research was carried out at the BPKP Representative of the Riau Islands Province. The research was conducted using quantitative methods using SPSS statistical tools, the number of samples was 100 auditors. The results of the study that (1) competence has a positive and significant effect on the Quality of Audit Results at BPKP Representatives of Riau Islands Province; (2) objectivity has a positive and significant effect on the quality of audit results at BPKP Representatives of Riau Islands Province; (3) time budget pressure has a positive and significant effect on the quality of audit results at BPKP Representatives of Riau Islands Province; (4) competence, objectivity, and time budget pressure have a positive and significant effect on the quality of audit results simultaneously at the Riau Islands Province BPKP Representative.